Interaction of Potent Mitochondrial Uncouplers with Thiol-Containing Antioxidants - Ljudmila S. Khailova; Alexander M. Firsov; Elena A. Kotova; Yuri N. Antonenko (MDPI AG, 2019)
It is generally considered that reactive oxygen species (ROS) are involved in the development of numerous pathologies. The level of ROS can be altered via the uncoupling of oxidative phosphorylation by using protonophores causing mitochondrial membrane depolarization. Here, we report that the uncoupling activity of potent protonophores, such as carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone (FCCP), carbonyl cyanide 3-chlorophenylhydrazone (CCCP), and fluazinam, can be abrogated by the addition of thiol-containing antioxidants to isolated mitochondria. In particular, N-acetylcysteine, glutathione, cysteine, and dithiothreitol removed both a decrease in the mitochondrial membrane potential and an increase in the respiration rate that is caused by FCCP. The thiols also reduced the electrical current that is induced by FCCP and CCCP across planar bilayer lipid membranes. Thus, when speculating on the mechanistic roles of ROS level modulation by mitochondrial uncoupling based on the antioxidant reversing certain FCCP and CCCP effects on cellular processes, one should take into account the ability of these protonophoric uncouplers to directly interact with the thiol-containing antioxidants.